SAT0337 Hypertrophic Pachymeningitis Associated with ANCA Vasculitis; A Case Series of 16 Patients. (15th July 2016) - Sakairi, T.; Hiromura, K.; Sakurai, N.; Hamatani, H.; Ikeuchi, H.; Kaneko, Y.; Maeshima, A.; Nojima, Y.
Abstract : Background: Recent reports indicate that hypertrophic pachymeningitis (HPM) develops in association with myeloperoxidase (MPO) anti-neutrophil cytoplasmic antibody (ANCA)-positive vasculitis 1, 2) . However, little is known about clinical features and outcomes of the disease. Objectives: We aimed to describe clinical, laboratory and radiological features and treatment course of HPM occurred in patients with ANCA-associated vasculitis (AAV). Methods: We retrospectively analyzed 16 Japanese adult patients (11 males and 5 females), who had been treated at our hospital in a study period from January 2006 through December 2015. Diagnosis of HPM was made with MRI T1 sequence with gadolinium by detecting thickening and enhancing of brain and/or spinal dura mater in patients manifesting neurological symptoms. Diagnosis and classification of AAV was performed according to a report by Watts, et.al. 3) . Results: The mean age at HPM onset was 60.1 years (range, 35–78 years). Out of 16 patients, HPM was detected at the onset of AAV in 9 (56.3%), at the relapsing AAV under treatment in 6 (37.5%), and before the diagnosis of AAV as idiopathic HPM in 1 (6.3%). Headache and cranial nerve palsy due to HPM were observed in 13 (81.3%) and 11 (68.8%) patients, respectively. Otitis media and sinusitis were found as complications of AAV in 7 (43.8%) and 6 (37.5%) patients. Twelve patients (75%) were classified as granulomatosis with polyangiitis (GPA). Microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis and unclassifiable vasculitis were applied to 2 (12.5%), 1 (6.3%) and 1 (6.3%) patients, respectively. Serum myeloperoxidase (MPO)-ANCA and proteinase 3 (PR3)-ANCA were positive in 9 (56.3%) and 5 (31.3%), respectively, and 2 (12.5%) patients had neither of them. The mean serum C-reactive protein levels were 4.87 mg/dL (range, 0.26–17.11 mg/dL). Spinal fluids were analyzed in 6 patients, and a mild increase in spinal cell counts and protein levels were identified in 3 patients each. With MRI, thickening of dura mater in cranial fossa and tentorium cerebelli were found in 11 (68.8%) and 9 (56.3%) patients, respectively. All patients were treated with corticosteroids and 10 (62.5%) patients were concomitantly administered with other agents including cyclophosphamide, methotrexate, azathioprine and mizoribine for remission induction. All patients achieved remission of the neurological symptoms and improvement of dura mater thickening. In a mean follow-up period of 41.8 months (range, 5–89 months) after diagnosis, 4 (25%) patients experienced a relapse of HPM and received re-induction therapy. Conclusions: Our results indicate that occurrence of HPM is mostly associated with GPA having either type of ANCA serology. Dura mater in cranial fossa and tentorium cerebelli was commonly involved, which could lead to cranial nerve impairment. Immunosuppressive therapy is effective, but a relapse of HPM occasionally occurs. References: Yokoseki A, et al. Brain. 2014 Feb;137(Pt2):520–36. Nagashima T, et al. Neuropathology. 2000 Mar;20(1):23–30. Watts R, et al. Ann Rheum Dis. 2007 Feb;66(2):222–7. Disclosure of Interest: None declared